2009
DOI: 10.1002/pen.21397
|View full text |Cite
|
Sign up to set email alerts
|

Impact fracture toughness and morphology of diatomite‐filled polypropylene composites

Abstract: Impact fracture strength is an important characterization for impact toughness of materials. A polypropylene (PP) filled with diatomite with different diameter (5, 7, and 13 lm) was fabricated by means a twinscrew extruder. The impact fracture strength of these composites was measured at room temperature to identify the effects of diatomite content and diameter on impact fracture strength of filled polypropylene composites. The results showed that the influence of diatomite on the notched impact strength was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Recently, the structure/property relationship nanometer CaCO 3 ‐filled PP composites has been paid extensive attention 8. More recently, one of us12 investigated the effects of the particle size and content of diatomite on the impact‐fracture toughness of filled PP composites, and got some interesting findings.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the structure/property relationship nanometer CaCO 3 ‐filled PP composites has been paid extensive attention 8. More recently, one of us12 investigated the effects of the particle size and content of diatomite on the impact‐fracture toughness of filled PP composites, and got some interesting findings.…”
Section: Introductionmentioning
confidence: 99%
“…PP is usually filled with inorganic particles to improve its mechanical properties including stiffness, strength, and toughness, such as calcium carbonate [4,5], glass bead [6][7][8][9], diatomite [10,11], Al(OH) 3 , and Mg(OH) 2 [12]. It was found that there were certain toughening effect [3,9,10] and reinforcing effect [6,8,11] of these inorganic particles in PP resin.…”
Section: Introductionmentioning
confidence: 98%
“…PP is usually blended with other resin [11] or filled with inorganic particles to improve its mechanical properties, including stiffness, strength and toughness. These inorganic particles include calcium carbonate [12,13], glass beads [14], diatomite [15][16][17], Al(OH) 3 and Mg(OH) 2 [18]. It was found that there were certain toughening effects [14,15] and reinforcing effect [11, 12, 16, …”
Section: Introductionmentioning
confidence: 99%